Cell Blocks from Ultrasound Guided Fine Needle Aspirates: Diagnostic Yield in a Series of 51 Dermatologic Lesions - A. Laverde-Saad; L. Nájera Botello; I. Salgüero Fernandez; L. Turrión Merino; G. Roustan Gullón; F. Alfageme Roldan (Elsevier, 2023)
The generation of cell blocks (CB) obtained from ultrasound-guided fine needle aspiration biopsies (USFNAB) is a well-established technique in breast and thyroid pathology, but is rarely used in dermatology. We reviewed CBs obtained from USFNAB of skin lesions, which were categorized as malignant skin tumors, benign skin tumors, inflammatory skin tumors or deposit skin diseases. The diagnostic yield of each category was compared to histopathology. The USFNAB of 51 skin lesions was processed into CBs. There was overall agreement between histopathology and CBs in 84.31% of cases. Diagnostic group concordance for benign, malignant as well as inflammatory and deposit skin lesions were 69.2%, 93.7% and 86.3% respectively. Cell block generation from USFNAB aspirates of skin lesions should be considered as part of the dermatologic diagnostic armamentarium. Further experience is needed to better understand for which types of dermatologic lesions it would be clearly indicated. Resumen: La generación de bloques celulares (CBs) obtenidos a partir de punción-aspiración con aguja fina guiada por ultrasonido (USFNAB), es una técnica bien establecida en patología mamaria y tiroidea, pero rara vez se utiliza en dermatología. Revisamos los CBs obtenidos por USFNAB de lesiones cutáneas, que se clasificaron como tumores cutáneos malignos, tumores cutáneos benignos, tumores cutáneos inflamatorios o enfermedades cutáneas por depósito. El rendimiento diagnóstico de cada categoría se comparó con la histopatología. La USFNAB de 51 lesiones cutáneas se procesó en CBs. Hubo concordancia global entre la histopatología y los CBs en el 84,31% de los casos. La concordancia entre histopatología y CBs para lesiones cutáneas benignas, malignas e inflamatorias y por depósito fue del 69,2, 93,7 y 86,3%, respectivamente. La generación de CBs a partir de USFNAB de lesiones cutáneas debe considerarse como parte del arsenal diagnóstico dermatológico. Se necesita más experiencia para comprender mejor para qué tipos de lesiones dermatológicas estaría claramente recomendado.